MEDIA FOTO UNTUK MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI SISWA SMA NEGERI 2 KEBUMEN - Rina Tri Indrianingrum; Suwarna Suwarna (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2015)
Penelitian ini bertujuan untuk menjelaskan meningkatnya keterampilan menulis deskripsi berbahasa Jawa siswa kelas X SMA N 2 Kebumen dengan menggunakan pendekatan proses dan media foto. Penelitian ini merupakan penelitian tindakan kelas atau classroom action research. Desain yang digunakan dalam penelitian ini adalah desain penelitian tindakan Kemmis dan Taggart. Penelitian ini dilaksanakan dua siklus. Subjek penelitian ini adalah siswa kelas X2 SMA Negeri 2 Kebumen tahun pelajaran 2011/2012 yang berjumlah 32 siswa. Pengumpulan data dilakukan dengan menggunakan observasi, catatan lapangan dan tes. Validitas yang digunakan adalah validitas demo-krasi, validitas proses dan validitas dialogis. Teknik yang digunakan untuk menganalisis data dalam penelitian tindakan ini adalah deskriptif. Hasil penelitian menunjukkan (1) siswa dapat menemukan ide lebih cepat, (2) siswa dapat membuat kerangka karangan, (3) siswa dapat mengembangkan kerang-ka karangan, (4) siswa dapat berpikir sistematis, (5) siswa semakin antusiasnya dalam mengikuti pembelajaran menulis karangan, (6) siswa paham melakukan proses mengarang. _________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________ PHOTOGRAPH MEDIA TO IMPROVE THE DESCRIPTION WRITING SKILL OF THE STUDENTS AT SMA NEGERI 2 KEBUMEN Abstract This research is aimed to describe and to explain the improvement in the description writing skill of the tenth grade students at SMA N 2 Kebumen by using approach process and photography media. This research is classroom action research or classroom action research. The design used in this research was action research design by Kemmis and Taggart. The subject of the research was X2 class students at SMA Negeri 2 Kebumen in the academic year of 2011/2012, consisted of 32 students. The data collection was done by using observation, field notes and description during the time of the learning activity and also tests (pre test and post test). The validity used was democratic validity because the researcher truthfully collaborated either with the teacher and the students, the research also used process validity, marked by accuracy in the research process and dialogic validity can be shown that the research was implemented by having dialogue with the teacher and the collaborator to seek for critics and suggestion. Reliability in this action research was based on contextual and situational and localized. The technique used to analyze the data in this action research was descriptive. The monitoring on the learning process shows that (1) the students can find ideas faster, (2) the students can make essay framework, (3) the students can develop essay framework, (4) the students can think systematically, (5) the students are more enthusiastic in attending the learning of writing essay, (6) the students understand the process of writing essay. Keywords: photography media, description writing.